KEPEMIMPINAN MASA DEPAN (FUTURE LEADERSHIP) DALAM PERSPEKTIF AGAMA, FILOSOFI, PSIKOLOGI DAN SOSIOLOGI; IMPLEMENTASINYA DALAM LEMBAGA PENDIDIKAN - Sujai, Akhmad; Rohim H.S., Abd.; Amrullah, Amrullah; Abdulhak, Ishak; Mudrikah, Achmad (Universitas Islam Syekh-Yusuf, 2021)
Change is a necessity. We must accept these changes with open arms. There is no other choice but to respond to the challenge of change by preparing various components to welcome it. Various resources must be prepared, especially in terms of human resources. We must prepare competent leadership who has a vision of the future that can answer these challenges. This study uses a descriptive qualitative methodology with a Library Research approach. The millennium has brought us many challenges and many opportunities for leadership. Leadership is no longer fixated on electing a few who are given power and authority. Each must be engaged to make full use of the knowledge and information that forms the basis of working life in the world of advanced technology in this century. Self-leadership is the key to enhancing learning which is necessary to enable us to face the challenges of a knowledge-based and information- rich age. Superleadership provides a tool for leaders to be able to create self-leadership in others. Religion plays a very important role in leadership. Anyone who enforces leadership, if it is done from a religious perspective, is actually continuing the prophetic mission (nubuwwah) and this applies throughout time. Becoming an effective leader requires a fairly complex process. Many factors influence the birth of future leaders. From a religious, philosophical, psychological and sociological perspective we will be able to see the importance of education in an effort to produce future leaders.